1998
DOI: 10.1038/sj.jhh.1000647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of losartan titrated to losartan/hydrochlorothiazide and amlodipine on blood pressure and peripheral capillary microcirculation in patients with mild-to-moderate hypertension

Abstract: Objective: To measure the effects of losartan and amlodipine on peripheral capillary microcirculation in hypertension. Setting: Medical out-patient clinic, Basel, in a university teaching hospital. Methods: After a 4-week placebo run-in period 20 patients aged 50 ± 8 (range 36-65) years with mild-tomoderate hypertension were randomly allocated to receive active treatment with losartan 50 mg titrated to losartan 50 mg/hydrochlorothiazide (HCT) 12.5 mg, or amlodipine 5 mg titrated to 10 mg for a 12 week period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the present study, lowering of systolic blood pressure during the inpatient treatment was associated with a reduction in resting CBV in Type 2 diabetic patients. This finding was unlikely as a result of antihypertensive medication used, because β‐blockers, angiotensin‐converting enzyme inhibitors and calcium antagonists did not appear to impair capillary perfusion in previous studies [24–26]. A limitation of the present study was that the heterogeneity of the patient populations with regard to diabetes duration and stages of diabetic complications might have influenced the differences between the microvascular data obtained in Type 1 and Type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, lowering of systolic blood pressure during the inpatient treatment was associated with a reduction in resting CBV in Type 2 diabetic patients. This finding was unlikely as a result of antihypertensive medication used, because β‐blockers, angiotensin‐converting enzyme inhibitors and calcium antagonists did not appear to impair capillary perfusion in previous studies [24–26]. A limitation of the present study was that the heterogeneity of the patient populations with regard to diabetes duration and stages of diabetic complications might have influenced the differences between the microvascular data obtained in Type 1 and Type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 69%
“…In other studies no significant effect was observed on laser Doppler and capillary perfusion studies by amlodipine in patients with untreated mild to moderate essential hypertension. 26,27 On the other hand, in one of our patients edema developed due to amlodipine replacement, which is a known cause of diminution of peripheral perfusion as a result of tissue pressure.…”
Section: Discussionmentioning
confidence: 79%
“…However, studies have demonstrated that in patients with hypertension, both ACE inhibitors and ARBs increase the finger nail-fold capillary blood cell velocity, which may play some role in this phenomenon. [15][16] Investigators have suggested that these effects on peripheral capillary microcirculation occur through modulation of catecholamines.…”
Section: Discussionmentioning
confidence: 99%